Pengaruh Penggunaan Media Audio Visual Terhadap Minat Belajar Siswa pada Mata Pelajaran PAI: SDN Cihideung Udik 01 Kelas VI A Kab.Bogor - Sultan Abdul Azis; Indriya; Muhammad Faishal Hidayat (Ikatan Dai Indonesia, 2025)
Media Known as a teaching tool that must be used by teachers, but is often ignored. There is no media used in the learning process, but generally it is done for various reasons. In the learning process, teachers must use media as a tool to make it easier for students to understand the material, but it is often ignored. In the learning process there is no media, but in general it is done because of reasons. There are many causes, for example in the limited learning time prepared, in finding media that is difficult to match and not available, and so on. The cause of the low interest in learning students in Islamic religious education subjects, low performance of educators so that it is less conducive. Although in schools that do not have an Islamic nuance, but in the curriculum there are Islamic religious education subjects, in delivering the material the educator is less affective so that students have a lack of interest in learning. This study aims to determine how the use of Audio visual learning media in Islamic Religious Education subjects affects learning interest at SDN Cihideung Udik 01 class VI A. This study uses quantitative methods. from the results of the study showed that the probability value of the audio-visual media variable is smaller than 0.05 and t count is greater than t table (15.208> 2.048). So it can be concluded that (X1) audio-visual media has a positive and significant effect on (Y) learning interest in students of SDN Cihideung Udik 01 Class VIA Kab Bogor. the F count value is 231.272 with a significance of 0.000. Because the level of significance is smaller than 0.05 and F count is greater than F table (231.272> 4.20). Then H0 is rejected, so it can be said that audio-visual media has a significant effect on learning interest.